Assessment of Carbon Emission Reduction for Buildings Projects in Malaysia-A Comparative Analysis - Klufallah, M.M.A. (EDP Sciences, 2014)
The Malaysian construction industry significantly contributes as an empowerment to its development vision of 2020 by reducing 40 of carbon emission. Moreover, this industry accounts as a threat to the environment, not only in terms of consumption of natural resources but also in emitting million tons of carbon emission annually. In fact, Malaysia is categorized the 30th in the world's ranking in carbon emission level. To mitigate the raise of carbon emission level from the buildings construction, several studies identified some of the effective carbon emission assessment tools for construction projects but it is lack of implementation in Malaysia. The green building index (GBI), Malaysian CIB Report has been introduced to assist the construction stakeholders in reducing the level of carbon emission and the impact of buildings on the environment. This paper presents an analysis of carbon emission from housing projects and office buildings in order to identify and quantify the main sources of carbon emission for each project and it proposes environmental friendly materials as replacement for conventional construction materials to achieve the implementation of sustainability in Malaysia. Â© 2014 Owned by the authors, published by EDP Sciences.